Design features and technology of installation of new spatial constructions of composite grid-cable coverings - Стороженко, Леонид Иванович; Гасий, Григорий Михайлович; Гапченко, Сергей Андреевич (Eastern-European Journal of Enterprise Technologies, 2014)
Development of building sector accompanied by regular introduction new designs. An important factor in finding constructive solutions is the use of reliable, modern and lightweight materials. The main focus of scientists directed mainly to the study of tense-deformed state of beams, columns, slabs, bridge construction and civil engineering. Researches on the study of spatial composite structures is not enough. The study composite grid-cable coverings is the actual problem, because their mass use in the construction of buildings and structures would save materials and labor. Composite grid-cable coverings is space system that consists of plates and cross-rod trusses. Distinctive feature of the composite grid-cable coverings is guyed lower belt made of flexible elements, working only on tensile. Covering is collected of the individual lightweight structure elements. Manufacturing technology is divided into two independent processes: the production of steel lattice and the formation of the plate. Another distinctive feature of composite grid-cable coverings is their versatility by changing the lengths of the bottom member can be given different curvatures, buildings and structures is covered of any complexity and shape. Research confirms the effectiveness of constructive solutions coverings because labor costs of installation and materials decreased compared with analogues.